Use of Multi-Response Logistic Regression to Determine the Factors Affecting the Radiation Values of Light-Curing Units in Private Dental Clinics in Erbil - Yacoob, Ilham M.; Karyakos, Raed Sabeeh; Slewa, Muna Y. (Iraqi Journal of Science, 2022)
This study aims to determine the exposure of dentists to radiation resulting from the use of light therapy units and to assess their risk and impact on dental clinics.  This study was conducted in private dental clinics in the city of Erbil in northern Iraq. Surveys were conducted to collect information about light-curing units. The results were analysed using the multi-response logistic regression to determine the factors affecting the radiation values of light-curing units. The results of the study showed that five major variables have a major effect by radiation.  This is shown with a value of P ≤ 0.05. Typical treatment times with radiant light, with a typical number of daily restorations, may exceed the risk limits for blue light reflected on eyes. This is given that the responding dentists did not protect their eyes with enough blue light .Technology in dentistry requires the operator to have knowledge of basic technical specifications and the safe use of devices and tools routinely used in dental treatment.